Pós-modernidade, direitos humanos e alteridade: uma concepção multicultural - Reis, Milena Jackeline (2021)
Postmodernity brought to the world a new organization of communications, work, transportation, space versus time, among others. All these nuances of postmodernity influence human beings' relations with each other, as well as their surroundings, family, friends, work, community, since men and women are social beings. People are not born ready, not even finished, they are formed from relationships with other people, so much so that they have the same characteristics as themselves, as people who have characteristics or ways of living different from themselves. Therefore, alterity plays an important role in the construction of the essence of the human person. Postmodernity emphasizes the plurality and diversity of the ways of the different peoples that inhabit the terrestrial globe, at the same time that there is an attempt to standardize by Western hegemonic culture and individualism prevails. Human rights are historical achievements that have followed the development of human history, today they face challenges such as their effectiveness. Human rights, due to their philosophical historical origin, have a western origin and are currently hegemonic in character, perpetuating the status quo, partly losing their bias in the fight against those in power. In human rights theory there is still a dichotomy that needs to be overcome, namely, cultural relativism and universalism. Both conceptions (relativist or universalist) do not meet the primacy of otherness, nor do they even manage to contemplate the cultural diversity and plurality of the postmodern world. Multiculturalism would be the middle way, that is, a vision of human rights, more attentive to cultural plurality and otherness. The present work, therefore, intends to analyze the postmodernity, the otherness, the historical and philosophical origin of human rights, the conceptions of human rights, in order to understand why cultural relativism and universalism need to be overcome, so that human rights become more effective and represent all peoples and cultures